Dissertation - OKAO Jesse (Uganda Christian University, 2024)
This dissertation consists of five chapters. Chapter one consists of introduction of the variables, their scope and statement of the problem, objectives of the study, research questions and the scope of the study. Chapter two draws down the literature review of all the objectives. Chapter three narrates the methods of data collection, population size and sample size of the study population while chapter four and five crown data analysis, presentation, interpretation and discussion of research findings, conclusions, recommendations and spot areas of further research respectively. New times roman size 12 and 1.5 line spacing was used to compile this proposal. The scope of this study is restricted to the barriers of sustainable procurement in local governments in Uganda with general objectives such as highlighting the factors perceived to be the most important barriers to implementing sustainable procurement in local governments in Uganda, investigating the value or benefits of sustainable procurement practices in public sector organizations and developing proposed interventions aimed to successfully implement sustainable procurement practices. Some of the barriers of sustainable procurement include; lack of awareness, cost implication, availability of suppliers of sustainable products, tools or services, knowledge and capacity, structural and organizational change, effective supplier engagement among others. The benefits include; the control of costs through whole life costing, compliance with environmental legislation, management of risk, and competitive advantage among others. Some of the interventions aimed at successfully implementing sustainable procurement include; conducting initial training in key sustainable procurement principles and coming up with a sustainability criterion when awarding key contracts. The research was exploratory in nature and that is to say that it adopted both qualitative and quantitative methods of data collection. In qualitative, the researcher was able to analyze findings on the ground through interaction with the participants at the field in order to make the research study more meaningful while in quantitative method, the researcher presented the findings statistically in table form so as to make the analysis easy. A sample size of fifty-two (52) respondents was studied of which only thirty-seven (37) responded to the questionnaires issued to them. Fourteen respondents understood the concept of sustainable procurement while twenty-three had no idea about the concept and also didn’t observe any benefits articulated to sustainable procurement in the organization. However, the rest of the respondents stated some benefits of sustainable procurement such as; Value for money and the costs attributed to the procured products were controlled throughout its shelf life. The majority of them considered lack of top management support and sustainable procurement being a very costly venture as most important barriers to sustainable procurement. Amidst these barriers, the respondents suggested some interventions aimed at successfully implementing sustainable procurement including conducting initial training in key sustainable procurement principles and providing a sustainability criterion when awarding key contracts. The researcher discussed the results of the findings with respect to the general objectives of the study; he related his field findings with the literature review and found a good coloration between the two sets of data. He recommended these research findings to the students and all procurement practitioners, the organization and finally to the government. He also spotted areas of further research
The purpose of this study is to enhance understanding and explanations of barriers to sustainable procurement implementation in public sector or local governments in Uganda, determine the value of sustainable procurement in local governments in Uganda as well as to address these gaps in our knowledge and examine policy commitments and development at government organizational level.